Amorphous-nanocrystalline compact composite ceramic capable of improving irradiation volume change resistance of nuclear structure material and preparation method of amorphous-nanocrystalline compact composite ceramic
By introducing SIC nano-crystals to the amorphous SIOC powder, the amorphous-nanocrystalline dense compound ceramic is formed, which solves the problem of changes in volume changes in nuclear structure materials under the condition of radiation. Essence
Patent Information
- Application Number
- CN202411529130.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
AI Technical Summary
Nuclear structural materials will undergo volume changes under irradiation conditions, affecting the structural stability and comprehensive performance of the material, resulting in the stability and safety of the nuclear energy system being threatened.
By introducing SIC nano-crystals to the amorphous SIOC powder, the amorphous-nanocrystalline dense compound ceramic is formed, and the displacement damage characteristics and the interface stability of the non-crystal material are used to reduce the volume changes caused by radiation.
Effectively improve the ability to change the volume changes in the volume of nuclear structure materials, enhance the structural stability of the material and the fault tolerance capacity of radiation damage, and improve the comprehensive performance of the material under extreme radiation conditions.
Smart Images

Figure CN119371205A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of amorphous-nanocrystalline ceramic materials, and relates to an amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of nuclear structural materials to volume changes and a preparation method thereof. Background Art
[0002] Ceramic-based materials usually have excellent high-temperature structure, mechanical stability and corrosion resistance due to their strong covalent and ionic bonds. In particular, silicon carbide ceramics have a small absorption cross-section, low activation energy and good thermal conductivity under neutron irradiation conditions, and have excellent resistance to radiation damage. They are one of the best candidate materials for future nuclear structural materials.
[0003] Ceramic-based core structural materials can be divided into crystalline materials and amorphous materials. Among them, silicon carbide (SiC) is a crystalline ceramic with long-range ordered atomic arrangement and many crystal forms. In the 1970s, GR Hopkins and LHRovner et al. first proposed that SiC ceramics can be used as core structural materials for applications in extreme environments of high temperature and radiation; in addition, SiC fiber reinforced SiC (SiC f SiC / SiC composites have inherited many excellent properties of SiC ceramics, such as excellent resistance to radiation damage, and are also expected to be used in the field of nuclear materials. f / SiC composite materials are made by distributing SiC fibers in crystalline SiC, with crystalline SiC as the main phase. Such composite materials have high requirements on the quality of SiC fibers and demanding sintering conditions, and still face many challenges in the actual preparation and application process. For example, crystalline SiC ceramics show the common characteristics of crystal irradiation damage: when bombarded by high-energy particles, particles interact with lattice atoms to produce cascade damage, thereby generating lattice defects. The defects will migrate and aggregate, causing changes in the microstructure of the material, and even amorphization and radiation swelling will occur, significantly affecting the structural stability and comprehensive performance of the material. In contrast, many reported amorphous materials, such as SiO2 glass, borosilicate and alkali metal silicate glass, will not produce lattice defects under irradiation conditions, but will undergo certain microstructural rearrangements and volume shrinkage.
[0004] In summary, irradiation will cause changes in the volume of both crystalline and amorphous materials, thus affecting the structural stability and intrinsic properties of the materials, such as macroscopic size, mechanical properties, and thermodynamic stability. The destruction of the structural stability of nuclear materials will inevitably bring great uncertainty to the stability and safety of the nuclear energy system. Therefore, improving the material's resistance to radiation damage and structural stability is the key to ensuring the safe use of nuclear energy, and is also a problem currently faced by nuclear structural materials. Summary of the invention
[0005] In order to reduce the volume change of materials caused by radiation and improve the structural stability and radiation damage resistance of nuclear materials, the purpose of the present invention is to provide an amorphous-nanocrystalline dense composite ceramic and a preparation method for improving the radiation volume change resistance of nuclear structural materials.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] An amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of a core structure material to volume change, wherein the composite ceramic is prepared by introducing SiC nanocrystals into an amorphous SiOC powder, wherein the mass ratio of the amorphous SiOC powder to the SiC nanocrystals is 100:0.1-60, preferably 100:0.1-25, and more preferably 100:5-25
[0008] Furthermore, by introducing SiC nanocrystals into amorphous SiOC powder, mixing and then subjecting to heat treatment, a composite ceramic in which the nanocrystals are uniformly dispersed in the amorphous matrix and the size of the nanocrystals is controllable is obtained.
[0009] The heat treatment is to sinter the green body by hot pressing, the hot pressing sintering process is 1500-1600°C, the sintering pressure is 1.5-1.8T, and the sintering time is 1-3 hours.
[0010] A method for preparing an amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of nuclear structural materials to volume changes, by introducing SiC nanocrystals into amorphous SiOC powder, mixing and then subjecting to heat treatment to obtain a composite ceramic in which the nanocrystals can be uniformly dispersed in the amorphous matrix and the nanocrystal particle size is controllable.
[0011] Specifically
[0012] 1) preparing polysiloxane sol by hydrolysis using dimethyldimethoxysilane (CH3)2Si(OCH3)2 and methyltrimethoxysilane CH3Si(OCH3)3 as raw materials;
[0013] 2) drying the polysiloxane sol to convert it into a polysiloxane xerogel;
[0014] 3) Pyrolyzing the polysiloxane xerogel at high temperature to achieve inorganic transformation;
[0015] 4) Obtaining amorphous SiOC powder by ball milling and sieving process;
[0016] 5) uniformly mixing the amorphous SiOC powder and SiC nanocrystalline powder prepared above at a ratio of 100:0.1-60 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder;
[0017] 6) The amorphous-nanocrystalline mixed powder is pressed into a green body, and a SiOC / SiC amorphous-nanocrystalline dense composite ceramic is prepared by a hot pressing sintering process.
[0018] In the step 1), (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 are mixed in a mass ratio of 1:3.5-1:4.5, and then added to ethanol, and then water is added to the system to dissolve the alkoxysilane and mix thoroughly.
[0019] In the step 3), the obtained polysiloxane xerogel is subjected to high temperature pyrolysis for 2 to 3 hours under the protection of an inert gas, and the pyrolysis temperature is 800 to 1600° C. to obtain an amorphous SiOC block.
[0020] In the step 6), the hot pressing sintering process is 1500-1600° C., the sintering pressure is 1.5-1.8T, and the sintering time is 1-3 hours.
[0021] An application of the amorphous-nanocrystalline dense composite ceramic for improving the volume change resistance of nuclear structural materials under radiation, and the application of the composite ceramic in the preparation of radiation damage resistance, wave absorbing coating, lithium ion battery negative electrode material or sensor.
[0022] Compared with the prior art, the present invention has the following advantages and technical effects:
[0023] 1. The present invention prepares SiOC / SiC amorphous-nanocrystalline composite ceramics by using a method of SiC nanocrystals to strengthen amorphous SiOC, which combines the radiation damage characteristics of amorphous and crystalline materials, reduces the volume change caused by radiation to a certain extent, increases the "tolerance" of radiation damage of the material, and effectively improves the structural stability of the material under radiation conditions;
[0024] 2. The present invention uses amorphous SiOC and nanocrystalline SiC composed of basically the same elements to avoid excessive mixing of elements caused by irradiation; in addition, both are dominated by covalent bonds and ionic bonds, and SiOC can generate SiC crystal phase in situ through high-temperature heat treatment, which has excellent interface stability and matching; amorphous SiOC can serve as a defect trap to effectively accommodate the dislocated atoms emitted by the SiC crystal phase, thereby inhibiting the aggregation of crystal phase defects.
[0025] 3. The SiOC / SiC amorphous-nanocrystalline composite ceramic obtained by the present invention has amorphous SiOC as the main phase, and SiC nanocrystals are dispersed in the amorphous matrix; during the preparation process, the amorphous SiOC phase plays the role of an adhesive, which is conducive to the preparation of a dense composite material; under extreme irradiation conditions, the SiC crystal phase in the SiOC / SiC amorphous-nanocrystalline composite ceramic will undergo amorphization, and at the same time, the amorphous SiOC crystal will also crystallize to generate SiC nanocrystals, which greatly improves the "fault tolerance" and structural stability of the material's irradiation damage;
[0026] 4. The composite ceramics obtained by the present invention have a high-density amorphous-nanocrystalline interface, uniform nanocrystal particle size, uniform size, dispersed distribution of nanocrystals, and high density; and have excellent mechanical properties, high-temperature stability (~1300°C) and high-temperature oxidation resistance; at the same time, the preparation method is simple and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A process flow chart of the preparation of SiOC / SiC amorphous-nanocrystalline composite ceramics provided in an embodiment of the present invention;
[0028] Figure 2 This is a SEM photo of amorphous SiOC powder provided in an embodiment of the present invention;
[0029] Figure 3 TG-MS analysis of the gas products of high temperature pyrolysis of polysiloxane xerogel provided in the embodiment of the present invention;
[0030] Figure 4 The particle size distribution of the amorphous SiOC ceramic powder provided in the embodiment of the present invention;
[0031] Figure 5 A SEM photo of SiC nanocrystals in a SiOC / SiC amorphous-nanocrystalline mixed powder provided in an embodiment of the present invention;
[0032] Figure 6 The porosity and density distribution of SiOC / SiC amorphous-nanocrystalline composite ceramics provided in the embodiments of the present invention;
[0033] Figure 7 GIXRD diagram of SiOC / SiC amorphous-nanocrystalline composite ceramic provided by an embodiment of the present invention;
[0034] Figure 8 The nanocrystal size of SiOC / SiC amorphous-nanocrystalline composite ceramic provided in the embodiment of the present invention;
[0035] Fig. 9 The mechanical properties test results of the SiOC / SiC amorphous-nanocrystalline composite ceramic provided in the embodiment of the present invention;
[0036] Fig.10 The free volume changes of amorphous SiOC and SiOC / SiC amorphous-nanocrystalline composite ceramics before and after irradiation provided by the embodiments of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0038] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0039] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0040] The present invention makes full use of the difference in the response of crystalline materials and amorphous materials to radiation damage, and combines the composite materials formed by the two with their respective radiation damage characteristics, thereby reducing the volume change caused by radiation to a certain extent. In addition, the present invention improves the material's resistance to radiation damage by increasing the amorphous-crystalline interface density; specifically, the amorphous SiOC ceramic prepared by the precursor pyrolysis method is used as the matrix, SiC nanocrystals are pre-introduced into the matrix, and then high-temperature heat treatment is performed to adjust the size, distribution and proportion of SiC nanocrystals in the material, thereby realizing the controllable preparation of SiOC / SiC amorphous-nanocrystalline composite materials.
[0041] See also Figure 1 , combined with the process flow chart, the preparation method of the amorphous-nanocrystalline dense composite ceramic of the present invention is described, comprising the following steps:
[0042] 1) Preparation of polysiloxane sol: (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 were mixed in a mass ratio and added to 10wt% ethanol, and then deionized water was slowly added to the system to completely mix and hydrolyze, and the obtained solution was stirred at a constant temperature for 0.5 hours to fully mix;
[0043] 2) gelation of polysiloxane sol: drying the obtained sol in an oven at 70° C. for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0044] 3) High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel was pyrolyzed at high temperature for 2 hours under the protection of inert gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0045] 4) Powdering the amorphous SiOC block: crushing, grinding and sieving the obtained amorphous SiOC block to obtain amorphous SiOC powder;
[0046] 5) Preparation of SiOC / SiC amorphous-nanocrystalline mixed powder: Amorphous SiOC powder and SiC nanocrystals (particle size of 40 nm) were uniformly mixed according to a certain mass percentage to obtain SiOC / SiC amorphous-nanocrystalline mixed powder.
[0047] 6) Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: After the obtained SiOC / SiC amorphous-nanocrystalline powder is die-cast, it is prepared by a hot pressing sintering process at a temperature of 1500-1600°C, a pressure of 1.5-1.8T, and a time of 1-3 hours to finally obtain SiOC / SiC amorphous-nanocrystalline dense bulk ceramics.
[0048] Example 1
[0049] In this example, SiOC / SiC amorphous-nanocrystalline mixed powder containing 5wt% SiC nanocrystals is prepared, the sintering temperature is 1600°C, the sintering pressure is 1.8T, the sintering time is 3 hours, and finally a SiOC / SiC amorphous-nanocrystalline dense bulk ceramic sintering with sample number S3 is prepared. The specific steps are as follows:
[0050] Step 1: Preparation of polysiloxane sol: (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 are added to 10wt% ethanol as a solvent, and then deionized water is slowly added to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and the obtained solution is stirred at a constant temperature for 0.5 hours to allow it to be fully mixed;
[0051] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0052] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel is pyrolyzed at high temperature for 2 hours under the protection of inert Ar gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0053] Step 4: Powderization of amorphous SiOC block: The obtained amorphous SiOC block is crushed, ground and sieved to obtain micron-sized amorphous SiOC powder (see Figure 2 );
[0054] Step 5: Preparation of SiOC / SiC amorphous-nanocrystalline mixed powder: uniformly mix amorphous SiOC powder and SiC nanocrystals at a mass percentage of 100:5 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder.
[0055] Step 6: Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: The obtained SiOC / SiC amorphous-nanocrystalline mixed powder is die-cast into a green body with a thickness of about 5-8mm in a mold with a diameter of 30mm using 5MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1600℃, a pressure of 1.8T, and a time of 3 hours to finally obtain SiOC / SiC amorphous-nanocrystalline dense bulk ceramics.
[0056] Depend on Figure 2 The SEM photograph of micron-sized amorphous SiOC powder was obtained after the amorphous SiOC block was crushed, ground and sifted. It can be found that smaller amorphous SiOC powder can be obtained through the crushing, grinding and sifting processes in the experiment, which is conducive to the uniform mixing of amorphous SiOC powder and SiC nanocrystalline powder.
[0057] Example 2
[0058] In this example, SiOC / SiC amorphous-nanocrystalline mixed powder containing 10wt% SiC nanocrystals is prepared, the sintering temperature is 1600°C, the sintering pressure is 1.8T, the sintering time is 3 hours, and finally a SiOC / SiC amorphous-nanocrystalline dense bulk ceramic sintering with sample number S4 is prepared. The specific steps are as follows:
[0059] Step 1: Preparation of polysiloxane sol: (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 are added to 10wt% ethanol as a solvent, and then deionized water is slowly added to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and the obtained solution is stirred at a constant temperature for 0.5 hours to allow it to be fully mixed;
[0060] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0061] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel is pyrolyzed at high temperature for 2 hours under the protection of inert Ar gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0062] Step 4: Powderization of amorphous SiOC block: crushing, grinding and sieving the obtained amorphous SiOC block to obtain micron-sized amorphous SiOC powder;
[0063] Step 5: Preparation of SiOC / SiC amorphous-nanocrystalline mixed powder: uniformly mix amorphous SiOC powder and SiC nanocrystals at a mass percentage of 100:10 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder.
[0064] Step 6: Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: The obtained SiOC / SiC amorphous-nanocrystalline mixed powder is die-cast into a green body with a thickness of about 5-8mm in a mold with a diameter of 30mm using 5MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1600℃, a pressure of 1.8T, and a time of 3 hours to finally obtain SiOC / SiC amorphous-nanocrystalline dense bulk ceramics.
[0065] Example 3
[0066] In this example, SiOC / SiC amorphous-nanocrystalline mixed powder containing 15wt% SiC nanocrystals is prepared, the sintering temperature is 1600℃, the sintering pressure is 1.8T, the sintering time is 3 hours, and finally a SiOC / SiC amorphous-nanocrystalline dense bulk ceramic sintering with sample number S5 is prepared. The specific steps are as follows:
[0067] Step 1: Preparation of polysiloxane sol: Add (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 to 10wt% ethanol as a solvent, and then slowly add deionized water to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and stir the obtained solution at a constant temperature for 0.5 hours to fully mix it;
[0068] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0069] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel is pyrolyzed at high temperature for 2 hours under the protection of inert Ar gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0070] Step 4: Powderization of amorphous SiOC block: crushing, grinding and sieving the obtained amorphous SiOC block to obtain micron-sized amorphous SiOC powder;
[0071] Step 5: Preparation of SiOC / SiC amorphous-nanocrystalline mixed powder: Amorphous SiOC powder and SiC nanocrystals are uniformly mixed in a mass percentage of 100:15 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder.
[0072] Step 6: Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: The obtained SiOC / SiC amorphous-nanocrystalline mixed powder is die-cast into a green body with a thickness of about 5-8mm in a mold with a diameter of 30mm using 5MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1600℃, a pressure of 1.8T, and a time of 3 hours to finally obtain SiOC / SiC amorphous-nanocrystalline dense bulk ceramics.
[0073] Example 4
[0074] In this example, SiOC / SiC amorphous-nanocrystalline mixed powder containing 20wt% SiC nanocrystals is prepared, the sintering temperature is 1600°C, the sintering pressure is 1.8T, the sintering time is 3 hours, and finally a SiOC / SiC amorphous-nanocrystalline dense bulk ceramic sintering with sample number S6 is prepared. The specific steps are as follows:
[0075] Step 1: Preparation of polysiloxane sol: Add (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 to 10wt% ethanol as a solvent, and then slowly add deionized water to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and stir the obtained solution at a constant temperature for 0.5 hours to fully mix it;
[0076] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0077] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel is pyrolyzed at high temperature for 2 hours under the protection of inert Ar gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0078] Step 4: Powderization of amorphous SiOC block: The obtained amorphous SiOC block is crushed, ground and sieved to obtain micron-sized amorphous SiOC powder. The powder SEM is as follows: Figure 2 As shown;
[0079] Step 5: Preparation of SiOC / SiC amorphous-nanocrystalline mixed powder: uniformly mix amorphous SiOC powder and SiC nanocrystals at a mass percentage of 100:20 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder.
[0080] Step 6: Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: The obtained SiOC / SiC amorphous-nanocrystalline mixed powder is die-cast into a green body with a thickness of about 5-8mm in a mold with a diameter of 30mm using 5MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1600℃, a pressure of 1.8T, and a time of 3 hours to finally obtain SiOC / SiC amorphous-nanocrystalline dense bulk ceramics.
[0081] Example 5
[0082] In this example, SiOC / SiC amorphous-nanocrystalline mixed powder containing 25wt% SiC nanocrystals is prepared, the sintering temperature is 1600°C, the sintering pressure is 1.8T, the sintering time is 3 hours, and finally a SiOC / SiC amorphous-nanocrystalline dense bulk ceramic sintering with sample number S7 is prepared. The specific steps are as follows:
[0083] Step 1: Preparation of polysiloxane sol: Add (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 to 10wt% ethanol as a solvent, and then slowly add deionized water to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and stir the obtained solution at a constant temperature for 0.5 hours to fully mix it;
[0084] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0085] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel was pyrolyzed at high temperature for 2 hours under the protection of inert Ar gas at a pyrolysis temperature of 1600°C. The pyrolysis products and thermogravimetric changes are shown in the following table. Figure 3 As shown, an amorphous SiOC block is finally obtained;
[0086] Step 4: Powderization of amorphous SiOC block: The obtained amorphous SiOC block is crushed, ground and sieved to obtain micron-sized amorphous SiOC powder. The powder particle size distribution is as follows: Figure 4 As shown;
[0087] Step 5: Preparation of SiOC / SiC amorphous-nanocrystalline mixed powder: Amorphous SiOC powder and SiC nanocrystals are uniformly mixed at a certain mass percentage of 100:25 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder (see Figure 5 ).
[0088] Step 6: Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: The obtained SiOC / SiC amorphous-nanocrystalline mixed powder is die-cast into a green body with a thickness of about 5-8mm in a mold with a diameter of 30mm using 5MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1600℃, a pressure of 1.8T, and a time of 3 hours to finally obtain SiOC / SiC amorphous-nanocrystalline dense bulk ceramics.
[0089] Depend on Figure 3 When preparing SiOC / SiC amorphous-nanocrystalline dense bulk ceramics, TG-MS analysis of the gas products of polysiloxane xerogel pyrolysis at ~1600K shows that methane and hydrogen gas products are mainly released at 500-900℃, followed by a small amount of methyl radicals and hydrogen radicals. It can be concluded that the complete pyrolysis of the xerogel can be ensured by pyrolyzing the polysiloxane xerogel at 900℃ for a sufficient time, thereby achieving the inorganic transformation of the xerogel and generating amorphous SiOC.
[0090] Depend on Figure 4 The particle size distribution of amorphous SiOC powder after the amorphous SiOC block is crushed, ground and sifted. It can be seen from the figure that the particle size of amorphous SiOC powder is mostly distributed between 1 and 500 μm. It can be found that micron-level amorphous SiOC powder can be obtained through the crushing, grinding and sifting processes in the experiment, which is conducive to the uniform mixing of amorphous SiOC powder and SiC nanocrystals.
[0091] Depend on Figure 5 SEM photo of SiC nanocrystals in SiOC / SiC amorphous-nanocrystalline mixed powder with a mass percentage of 100:25. It can be found from the figure that the size of SiC nanocrystals is about 40nm, and they are dispersed on the amorphous SiOC micron powder by mechanical mixing, which helps to evenly mix the amorphous SiOC powder and SiC nanocrystals.
[0092] In summary, the polysiloxane xerogel and amorphous SiOC obtained in each step in each embodiment have the same characteristics.
[0093] Comparative Example 1
[0094] In this example, only amorphous SiOC powder is added, and SiC nanocrystals are not added. The sintering temperature is 1500°C, the sintering pressure is 1.5T, and the sintering time is 1 hour. Finally, the amorphous SiOC nanocrystal dense bulk ceramic sintering with sample number S1 is prepared. The specific steps are as follows:
[0095] Step 1: Preparation of polysiloxane sol: Add (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 to 10wt% ethanol as a solvent, and then slowly add deionized water to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and stir the obtained solution at a constant temperature for 0.5 hours to fully mix it;
[0096] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0097] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel is pyrolyzed at high temperature for 2 hours under the protection of inert gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0098] Step 4: Powderization of amorphous SiOC block: crushing, grinding and sieving the obtained amorphous SiOC block to obtain micron-sized amorphous SiOC powder;
[0099] Step 5: Sintering of dense bulk ceramics: The obtained amorphous SiOC powder is die-cast into a green body with a thickness of about 5-8 mm in a mold with a diameter of 30 mm using 5 MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1500°C, a pressure of 1.5T, and a time of 1 hour to finally obtain amorphous SiOC nanocrystalline dense bulk ceramics.
[0100] Comparative Example 2
[0101] In this example, only amorphous SiOC powder is added, and SiC nanocrystals are not added. The sintering temperature is 1600°C, the sintering pressure is 1.8T, and the sintering time is 3 hours. Finally, the amorphous SiOC nanocrystal dense bulk ceramic sintering with sample number S2 is prepared. The specific steps are as follows:
[0102] Step 1: Preparation of polysiloxane sol: Add (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 in a mass ratio of 1:4 to 10wt% ethanol as a solvent, and then slowly add deionized water to the solvent to completely mix and hydrolyze the alkoxysilane in the system, and stir the obtained solution at a constant temperature for 0.5 hours to fully mix it;
[0103] Step 2: gelation of polysiloxane sol: drying the obtained sol in an oven at 70°C for 12 hours to remove excess solvent and polycondensation products to obtain polysiloxane xerogel;
[0104] Step 3: High-temperature pyrolysis of polysiloxane xerogel: The obtained xerogel is pyrolyzed at high temperature for 2 hours under the protection of inert gas at a pyrolysis temperature of 1600°C to obtain an amorphous SiOC block;
[0105] Step 4: Powderization of amorphous SiOC block: crushing, grinding and sieving the obtained amorphous SiOC block to obtain micron-sized amorphous SiOC powder;
[0106] Step 5: Sintering of SiOC / SiC amorphous-nanocrystalline dense bulk ceramics: The obtained amorphous SiOC powder is die-cast into a green body with a thickness of about 5-8 mm in a mold with a diameter of 30 mm using 5 MPa. After die-casting, it is prepared by hot pressing sintering process at a temperature of 1600°C, a pressure of 1.8T, and a time of 3 hours to finally obtain amorphous SiOC nanocrystalline dense bulk ceramics.
[0107] The ceramic bodies prepared in the above examples and comparative examples were measured, see Figure 6-8 :
[0108] Depend on Figure 6 It can be seen that the ceramic density and porosity test results of each embodiment and comparative example are obtained. It can be seen from the figure that the density of the bulk ceramic is about 2.0-2.3 g / cm 3 , the porosity is about 2.0-2.3%; in addition, it can be concluded that with the increase of SiC nanocrystal content, the increase of sintering temperature and pressure, and the extension of sintering time, it is helpful to prepare high-density, low-porosity dense SiOC / SiC amorphous-nanocrystalline bulk ceramics.
[0109] Depend on Figure 7 It can be seen that the ceramic GIXRD spectra obtained in each embodiment and comparative example show that three strong peaks appear at 2θ=35.6°, 60.0° and 71.7°, corresponding to the diffraction characteristic peaks of the (111), (220) and (311) crystal planes of 3C-SiC nanocrystals, respectively; in addition, the three strong peaks are enhanced with the increase of the added 3C-SiC nanocrystal content, sintering temperature, pressure and time. The results show that the controllable preparation of SiOC / SiC amorphous-nanocrystalline bulk ceramics can be achieved by regulating the SiC nanocrystal content, sintering temperature and pressure, and sintering time.
[0110] Depend on Figure 8 It can be seen that the average grain size of ceramic 3C-SiC nanocrystals is obtained in each embodiment and comparative example. It can be seen from the figure that 3C-SiC nanocrystals are generated in each obtained product, and the average size of 3C-SiC nanocrystals increases with the increase of the added 3C-SiC nanocrystal content, sintering temperature, pressure and time, indicating that the controllable preparation of SiOC / SiC amorphous-nanocrystalline bulk ceramics can be achieved by regulating the SiC nanocrystal content, sintering temperature and pressure, and sintering time, and the introduction of nanocrystals content and size will significantly affect the SiC nanocrystal content and size in SiOC / SiC amorphous-nanocrystalline bulk ceramics.
[0111] It can be seen that compared with the ceramic block sintered by adding only amorphous SiOC powder, the present invention realizes the controllable preparation of amorphous-nanocrystalline composite materials by introducing SiC nanocrystals into amorphous SiOC powder, and can efficiently optimize the composition ratio, crystal phase purity and amorphous-nanocrystalline interface density of the amorphous-nanocrystalline composite materials by regulating the content and size of the introduced SiC nanocrystals.
[0112] The performance of the ceramics obtained in the above examples and comparative examples was further measured:
[0113] 1) Mechanical property determination, specifically: the hardness and modulus of the above examples S1-S7 were determined by nanoindentation characterization method, the SPM mode was selected as the test mode, the loading force was about 8mN, and the maximum indentation depth was in the range of 150-250nm.
[0114] Depend on Fig. 9 It can be seen that the ceramic hardness and modulus are obtained in each embodiment and comparative example, and the modulus of the dense bulk material is about 90-110 GPa, and the hardness is about 11-13 GPa; in addition, adding 3C-SiC nanocrystalline content, sintering temperature, pressure and time help to improve the mechanical properties of amorphous-nanocrystalline materials and ensure the safety of the materials when used under extreme conditions.
[0115] 2) Determination of the free volume of the samples before and after irradiation, specifically: the dimensional changes of the free volume inside the ceramic matrix of the above-mentioned examples S2, S4 and S7 samples before and after irradiation were characterized by a positron annihilation lifetime spectrum tester. The S2, S4 and S7 samples represent SiOC / SiC amorphous-nanocrystalline ceramics containing 0wt%, 10wt% and 25wt% SiC nanocrystals, respectively. The samples were sintered at 1600°C, 1.8T and 3 hours. The irradiation conditions were 516MeV Xe 31+ The ions were irradiated at room temperature with a dose of 2×10 13 Ion cm -2 .
[0116] Depend on Fig.10 It can be seen that the free volume changes of the obtained S2, S4 and S7 samples before and after high-energy particle irradiation show that the free volume of pure amorphous SiOC shrinks after irradiation. With the introduction of SiC nanocrystals, the shrinkage of the free volume of the material after irradiation decreases, and even when the mass fraction of SiC nanocrystals is 25wt%, the free volume increases slightly, indicating that the SiOC / SiC amorphous-nanocrystalline composite ceramics are prepared by the method of SiC nanocrystals enhancing amorphous SiOC, and the radiation damage characteristics of amorphous and crystalline materials are combined to reduce the volume change caused by radiation to a certain extent, increase the "fault tolerance" of the material's radiation damage, and effectively improve the structural stability of the material under irradiation conditions. The results verify the design concept of the patent application.
[0117] It can be seen from the above performance measurement results that compared with the ceramic block sintered by adding only amorphous SiOC powder, the amorphous-nanocrystalline composite ceramic prepared by introducing SiC nanocrystals into amorphous SiOC powder in the present invention can improve the material density and compactness in the same synthesis process. At the same time, due to the addition of nanocrystalline phase, the modulus and hardness of the material are improved, and the mechanical properties of the material are optimized. In addition, the SiOC / SiC amorphous-nanocrystalline composite ceramic prepared by the present invention combines the radiation damage characteristics of amorphous and crystalline materials, reduces the volume change caused by radiation to a certain extent, and effectively improves the structural stability of the material under radiation conditions.
[0118] In summary, the method of the present invention achieves controllable preparation of SiOC / SiC amorphous-nanocrystalline composite materials by pre-introducing SiC nanocrystals into the matrix and then heating at high temperature to adjust the size, distribution and proportion of SiC nanocrystals in the material. The nanocrystal particle size can be adjusted by heat treatment process and the size of introduced nanocrystals. The obtained dense composite ceramic containing high-density amorphous-nanocrystalline interface combines the characteristics of volume swelling of crystalline materials and volume shrinkage of amorphous materials after radiation damage, which can effectively reduce the volume change caused by radiation, increase the "fault tolerance" of radiation damage of materials, and effectively improve the structural stability of materials under radiation conditions; in addition, high-density amorphous-nanocrystalline interface can effectively improve the radiation damage resistance of materials. And the SiOC / SiC amorphous-nanocrystalline composite ceramic material prepared by this method can be used in the fields of radiation damage resistance, wave absorbing coating, lithium ion battery negative electrode material, sensor, etc. in the form of coating, structural material parts, etc. The SiOC / SiC amorphous-nanocrystalline ceramic and the preparation method thereof disclosed in the present invention have the advantages of simple process, high-density amorphous-nanocrystalline interface, uniform nanocrystalline grain size, uniform size, dispersed distribution of nanocrystalline and high density, and are suitable for large-scale production; in addition, in terms of material selection, amorphous SiOC and nanocrystalline SiC are basically composed of the same elements, which can avoid the transitional mixing of elements caused by irradiation; in addition, both are dominated by covalent bonds and ionic bonds, and SiOC can generate SiC crystal phase in situ through high-temperature heat treatment, and has excellent interface stability and matching; amorphous SiOC can be used as a defect trap to effectively accommodate the dislocated atoms emitted by the SiC crystal phase, and inhibit the aggregation of crystal phase defects; in terms of design concept, the radiation damage characteristics of amorphous and crystalline materials are combined to reduce the volume change caused by radiation to a certain extent, increase the "fault tolerance" of the material radiation damage, and effectively improve the structural stability of the material under irradiation conditions.
[0119] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. An amorphous-nanocrystalline dense composite ceramic for improving the volume change resistance of nuclear structural materials to radiation, characterized in that: The composite ceramic is prepared by introducing SiC nanocrystals into amorphous SiOC powder, wherein the mass ratio between the amorphous SiOC powder and the SiC nanocrystals is 100:0.1-60.
2. The amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of nuclear structural materials to volume change according to claim 1, characterized in that: The SiC nanocrystals are introduced into the amorphous SiOC powder, mixed and then heat treated to obtain the composite ceramics in which the nanocrystals are uniformly dispersed in the amorphous matrix and the nanocrystal grain size is controllable.
3. The amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of nuclear structural materials to volume change according to claim 2, characterized in that: The heat treatment is to sinter the green body by hot pressing, the hot pressing sintering process is 1500-1600°C, the sintering pressure is 1.5-1.8T, and the sintering time is 1-3 hours.
4. A method for preparing an amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of nuclear structural materials to volume change according to claim 1, characterized in that: By introducing SiC nanocrystals into amorphous SiOC powder, mixing and then subjecting to heat treatment, a composite ceramic in which the nanocrystals are uniformly dispersed in the amorphous matrix and the nanocrystal grain size is controllable is obtained.
5. The method for preparing amorphous-nanocrystalline dense composite ceramics for improving the radiation resistance of nuclear structural materials to volume change according to claim 4, characterized in that: 1) preparing polysiloxane sol by hydrolysis using dimethyldimethoxysilane (CH3)2Si(OCH3)2 and methyltrimethoxysilane CH3Si(OCH3)3 as raw materials; 2) drying the polysiloxane sol to convert it into a polysiloxane xerogel; 3) Pyrolyzing the polysiloxane xerogel at high temperature to achieve inorganic transformation; 4) Obtaining amorphous SiOC powder by ball milling and sieving process; 5) uniformly mixing the amorphous SiOC powder and SiC nanocrystalline powder prepared above at a ratio of 100:0.1-60 to obtain SiOC / SiC amorphous-nanocrystalline mixed powder; 6) The amorphous-nanocrystalline mixed powder is pressed into a green body, and a SiOC / SiC amorphous-nanocrystalline dense composite ceramic is prepared by a hot pressing sintering process.
6. The method for preparing amorphous-nanocrystalline dense composite ceramics for improving the radiation resistance of nuclear structural materials to volume change according to claim 5, characterized in that: In the step 1), (CH3)2Si(OCH3)2 and CH3Si(OCH3)3 are mixed in a mass ratio of 1:3.5-1:4.5, and then added to ethanol, and then water is added to the system to dissolve the alkoxysilane and mix thoroughly.
7. The method for preparing amorphous-nanocrystalline dense composite ceramics for improving the radiation resistance of nuclear structural materials to volume change according to claim 5, characterized in that: In the step 3), the obtained polysiloxane xerogel is subjected to high temperature pyrolysis for 2 to 3 hours under the protection of an inert gas, and the pyrolysis temperature is 800 to 1600° C. to obtain an amorphous SiOC block.
8. An application of the amorphous-nanocrystalline dense composite ceramic for improving the radiation resistance of nuclear structural materials to volume change according to claim 1, characterized in that: The composite ceramic is used in the preparation of radiation damage resistance, wave absorbing coating, lithium ion battery negative electrode material or sensor.
Citation Information
Patent Citations
Preparation method of amorphous SiOC ceramic powder
CN104291791A
Preparation method of SiOC aerogel
CN117003242A